2020
DOI: 10.1038/s41598-020-70255-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and brain damage during multiple sclerosis course: inflammatory activity is a key factor in the first 5 years

Abstract: Understanding of the role of focal inflammation, a treatable feature, on neuro-axonal injury, is paramount to optimize neuroprotective strategy in MS. To quantify the impact of focal inflammatory activity on the rate of neuro-axonal injury over the MS course. We quantified the annualized rates of change in peripapillary retinal nerve fiber layer, ganglion cell plus inner plexiform layer (GCIPL), wholebrain, gray matter and thalamic volumes in patients with and without focal inflammatory activity in 161 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…This cohort is described elsewhere, including detailed ophthalmologic examination. 6 , 13 Indeed, we analyzed 5 patients with NMO and anti–aquaporin-4 antibodies (NMO-AQP4) and 3 with myelin oligodendrocyte glicoprotein (MOG)-associated encephalitis (MOGAD) with anti-MOG antibodies, as described previously. 7 Regarding the healthy controls, we collected 34 healthy volunteers matched for sex and age with the MS cohort as well as 12 healthy volunteers older than 55 years to analyze the effect of age on each of the molecules.…”
Section: Methodsmentioning
confidence: 99%
“…This cohort is described elsewhere, including detailed ophthalmologic examination. 6 , 13 Indeed, we analyzed 5 patients with NMO and anti–aquaporin-4 antibodies (NMO-AQP4) and 3 with myelin oligodendrocyte glicoprotein (MOG)-associated encephalitis (MOGAD) with anti-MOG antibodies, as described previously. 7 Regarding the healthy controls, we collected 34 healthy volunteers matched for sex and age with the MS cohort as well as 12 healthy volunteers older than 55 years to analyze the effect of age on each of the molecules.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Recent magnetic resonance imaging (MRI) and optical coherence tomography (OCT) studies have shown that most of the central nervous system (CNS) damage happens in the first 5 years after disease onset. 4,5 Brain volume loss is a predictor of future disability, 6 and this further endorses the early high-efficacy approach. Then, we need better diagnostic algorithms and informative biomarkers which will identify which patients are at higher risk of disease activity to personalize the therapeutic decision.…”
mentioning
confidence: 83%
“…[5][6][7][8][9] Brain volume loss generally showed positive predictive power on long-term MS progression, particularly regarding increases in EDSS score 10 and assessments that combine brain atrophy and retinal thinning. 11 Although assessments of gray matter reductions were also predictive of MS progression, the evidence was partially based on associations and correlations. 12,13 Similarly, there was some evidence supporting the predictive power of white matter on long-term disease progression, however it was based on associations.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Moccia 2016 16 1 Fraction of intracranial volume 2 One-point increase for EDSS score ≤ 5.5 and a 0.5-point increase (confirmed after at least 3 months) for EDSS score > 5.5 3 Compared to patients with NEDA (absence of relapses, of confirmed EDSS worsening and of MRI activity) 4 Evidence of disease activity: occurrence of ≥ 1 relapses with either confirmed EDSS worsening or ≥ 1 gadolinium-enhancing lesions or ≥3 new T2 lesions 5 Minimal evidence of disease activity: either 1 relapse with ≤2 new T2 lesions or < 3 new T2 lesions or < 2 gadolinium-enhancing lesions, in the absence confirmed EDSS worsening 6 NEDA-3: absence of new clinical relapse, disability progression, and active MRI lesions during follow-up, and no evidence of disease activity 7 Sustained disability progression was defined as an increase in EDSS by 1.0 point (if baseline EDSS score > 0) or 1.5 points (if baseline EDSS score = 0), confirmed after 12 months 8 NEDA-4: absence of new clinical relapse, disability progression, active MRI lesions as well as increased whole brain volume loss during followup 9 NEDA-4: no MRI lesion activity, no relapses, no confirmed progression of disability, and annual brain volume loss < 0.4% 10 NEDA-3: no MRI lesion activity, no relapses, and no confirmed progression of disability 11 Clinical NEDA: no relapses, and no EDSS worsening 12 NEDA-3a: no relapses and no new T2-active lesions during treatment, and no confirmed 1-point EDSS progression 13 NEDA-3B: no relapses and no EDSS/T2 burden of disease worsening 14 NEDA-a4: no relapses, no EDSS/T2 burden of disease worsening, and no enlargement in 3rd ventricle size…”
Section: O N L I N E I R S Tmentioning
confidence: 99%